Whatsapp messenger as mobile learning technique to the students’ writing skill in caption at SMAN 4 Bangkalan - Utami , Rina Aprilia (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2019)
The final project is based on a study which attempt to examine WhatsApp messenger as mobile learning technique to the students’ writing skill in caption at SMAN 4 Bangkalan in academic year of 2017/2018. This final project has an objective; how effective student’s used whatsapp messenger as mobile learning technique to writing ability. This study was conducted by using quantitative especially experimental method; there was form of pre-experimental research design. The researcher used some variables in research. The first was as the independent that was guiding whatsapp messenger as mobile learning technique and the second was as the dependent variable that was on students’ writing ability. The researcher used SPSS.23 for counting the result of test. The result showed that there was effect to the student’s writing ability by using whatsapp messenger as mobile learning technique. With regard to the previous result, it can be concluded that the teaching writing ability by using whatsapp messenger resulted a better achievement.